Validity and reliability of the Turkish version of the Innsbruck RBD-9 diagnostic inventory (IRBD-9-TR) - Kezban Aslan-Kara; Ayşın Kısabay Ak; Ayşegül Şeyma Sarıtaş; Hikmet Yılmaz; Kübra Mehel Metin; Burcu Gökçe Çokal; Kadriye Ağan; Murat Aksu; Utku Oğan Akyıldız; Aylin Bican Demir; Betül Çevik; Ahmet Yusuf Ertürk; et al. (Arquivos de Neuro-Psiquiatria)
Background Isolated rapid eye movement (REM) sleep behavior disorder (iRBD) is characterized by loss of the normal atonia of REM sleep accompanied by repetitive motor and behavior phenomena of dream content.